Structural and Functional Reorganization of the Brain in Migraine Without Aura - Soheili-Nezhad, Sourena; Sedghi, Alireza; Schweser, Ferdinand; Eslami Shahr Babaki, Amir; Jahanshad, Neda; Thompson, Paul M.; Beckmann, Christian F.; Sprooten, Emma; Toghae, Mansoureh (Frontiers in Neurology, 2019)
It remains unknown whether migraine headache has a progressive component in its pathophysiology. Quantitative MRI may provide valuable insight into abnormal changes in the migraine interictum and assist in identifying disrupted brain networks. We carried out a data-driven study of structural integrity and functional connectivity of the resting brain in migraine without aura. MRI scanning was performed in 36 patients suffering from episodic migraine without aura and 33 age-matched healthy subjects. Voxelwise analysis of regional brain volume was performed by registration of the T1-weighted MRI scans into a common study brain template using the tensor based morphometry (TBM) method. Changes in functional synchronicity of the brain networks were assessed using probabilistic independent component analysis (ICA). TBM revealed that migraine is associated with reduced volume of the medial prefrontal cortex (mPFC). Among 375 functional brain networks, resting-state connectivity was decreased between two components spanning the visual cortex, posterior insula, and the parietal somatosensory cortex. Our study reveals structural and functional alterations of the brain in the migraine interictum that may stem from underlying disease risk factors and the “silent” aura phenomenon. Longitudinal studies will be needed to investigate whether interictal brain changes are progressive and associated with clinical disease trajectories.